2022
DOI: 10.1503/cmaj.221335
|View full text |Cite
|
Sign up to set email alerts
|

Serial cross-sectional estimation of vaccine-and infection-induced SARS-CoV-2 seroprevalence in British Columbia, Canada

Abstract: The British Columbia Centre for Disease Control (BCCDC) has a longestablished serosurvey protocol to monitor population susceptibility to emerging or re-emerging respiratory viruses. The approach was first deployed during the influenza A (H1N1) pandemic in 2009 to monitor changes in seroprevalence across successive pandemic waves and the mass vaccination campaign. [1][2][3][4][5][6][7] The methodology is predicated upon serial cross-sectional convenience sampling of anonymized residual sera from children and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
63
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 48 publications
9
63
2
Order By: Relevance
“…Our Omicron IAR estimates over time were lower than those reported in South Africa (58% in urban areas by April 2022) 20 , Denmark (66% by March 2022) 21 , Navarre, Spain (up to 59% by May 2022) 22 and British Columbia, Canada (up to 61% by July–August 2022) 23 likely reflecting the effectiveness of extensive public health and social measures imposed in Hong Kong during the fifth wave, such as a universal mask mandate with high community compliance, closure of all bars, and limits on opening hours and new ventilation requirements in all restaurants 24 , counteracted by the very high density of Hong Kong’s residential dwellings facilitating rapid aerosol transmission between apartments 25 .…”
Section: Discussioncontrasting
confidence: 76%
“…Our Omicron IAR estimates over time were lower than those reported in South Africa (58% in urban areas by April 2022) 20 , Denmark (66% by March 2022) 21 , Navarre, Spain (up to 59% by May 2022) 22 and British Columbia, Canada (up to 61% by July–August 2022) 23 likely reflecting the effectiveness of extensive public health and social measures imposed in Hong Kong during the fifth wave, such as a universal mask mandate with high community compliance, closure of all bars, and limits on opening hours and new ventilation requirements in all restaurants 24 , counteracted by the very high density of Hong Kong’s residential dwellings facilitating rapid aerosol transmission between apartments 25 .…”
Section: Discussioncontrasting
confidence: 76%
“…27 Specifically, seroprevalence study in BC showed that at least 63% of children under the age of 5 were infected by March 2022, at time when few were vaccinated. 28 To the best of our knowledge, we could only compare our annual analysis findings with published literature due to unavailability of population-level studies since Omicron emerged. Our findings are similar to other studies reporting higher rates of hospitalisation for COVID-19 compared with influenza in unvaccinated populations in the early phases of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Among our BA.4/5 controls, we identified 15% with a prior infection compared to 40% in the same age group in sero-prevalence studies conducted in July-August 2022 in Quebec and British Columbia, Canada. 13,28 Missed prior infections in the reference group of unvaccinated "uninfected" individuals would result in underestimation of the protection induced by prior infection and hybrid immunity. VE among "uninfected" individuals would be underestimated if the proportion of missed prior infections among vaccinated individuals was smaller than the unvaccinated "uninfected" group, but would be overestimated if their proportion of missed prior infections was higher.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their greater risk of severe outcomes, elderly adults ≥60 years of age have been prioritized for COVID-19 vaccination since the start of the pandemic. Sero-prevalence data in Canada, the United States, United Kingdom and elsewhere show age-related decrease in cumulative SARS-CoV-2 infection rates across the pandemic [12][13][14][15] Infections foremost accrued during successive omicron waves, with at least 70% of Canadian children and young adults and about half of elderly adults having been infected by autumn 2022. 12,13 The accumulating percentage of the elderly population with prior history of both SARS-CoV-2 infection and repeat vaccination has likely modified their baseline risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation